Mitapivat in adult patients with pyruvate kinase deficiency receiving regular transfusions (ACTIVATE-T): a multicentre, open-label, single-arm, phase 3 trial. Issue 10 (October 2022) - Glenthøj, Andreas; van Beers, Eduard J; Al-Samkari, Hanny; Viprakasit, Vip; Kuo, Kevin H M; Galactéros, Frédéric; Chonat, Satheesh; Porter, John; Zagadailov, Erin; Xu, Rengyi; Oluyadi, Abdulafeez; Hawkins, Peter; et al.
Summary: Background: Mitapivat, an oral activator of pyruvate kinase (PK) in red blood cells (RBCs), has shown significant improvements in haemoglobin and haemolysis among patients with pyruvate kinase deficiency who were not receiving regular transfusions. We aimed to evaluate the efficacy and safety of mitapivat in adults with pyruvate kinase deficiency receiving regular transfusions. Methods: ACTIVATE-T was an open-label, single-arm, phase 3 trial conducted in 20 centres across Europe, North America, and Asia. Eligible participants were adults (aged ≥18 years) with a clinical laboratory confirmation of pyruvate kinase deficiency receiving regular transfusions (at least six episodes in the previous year). Participants received oral mitapivat during a 16-week dose-optimisation period (5 mg, 20 mg, 50 mg twice daily) and 24-week fixed-dose period. The primary endpoint was a reduction in transfusion burden (≥33% reduction in number of RBC units transfused during the fixed-dose period, compared with the participant's individual historical transfusion burden, standardised to 24 weeks). Efficacy and safety were assessed in all participants who received at least one dose of mitapivat. This trial is registered with ClinicalTrials.gov, NCT03559699, and is complete. Findings: Between June 26, 2018, and Feb 4, 2020, 27 participants (20 [74%] female and seven [26%] male; 20 [74%] White, three [11%] Asian, and four [15%] not reported) were enrolled and received at least one dose of mitapivat. Median duration of exposure to mitapivat was 40·3 weeks (IQR 40·0–41·3). A reduction in transfusion burden by at least 33% was found in ten (37%) participants (95% CI 19–58; p=0·0002). The most common treatment-emergent adverse events were increase in alanine aminotransferase (ten [37%] participants), headache (ten [37%]), increase in aspartate aminotransferase (five [19%]), fatigue (five [19%]), and nausea (five [19%]). Two grade 3 treatment-emergent adverse events were related to study treatment: joint swelling (one participant [4%]) and an increase in aspartate aminotransferase (one participant [4%]). Three participants had serious treatment-emergent adverse events, none related to the study treatment: increased blood triglycerides, ovarian cyst, and renal colic (each in one participant [4%]). No treatment-related deaths were observed. Interpretation: Mitapivat represents a novel therapy that can reduce transfusion burden in some adults with pyruvate kinase deficiency receiving regular transfusions, and is the first disease-modifying agent approved in this disease. Funding: Agios Pharmaceuticals.